Evaluasi Implementasi Kebijakan Naik Kelas Otomatis Pada Siswa Sekolah Dasar Di Kecamatan Cakung - Oktavia, Ovi; Amaliyah, Nurrohmatul (Cetta: Jurnal Ilmu Pendidikan, 2025)
The automatic grade promotion policy has been introduced in the implementation of the Merdeka Curriculum at the elementary school level to create inclusive and psychologically supportive learning environments. However, this policy has sparked debates regarding its effectiveness in maintaining educational quality. This study aims to evaluate the implementation of the automatic grade promotion policy in elementary schools in Cakung District, East Jakarta. The research employed a descriptive qualitative approach with a constructivist paradigm, utilizing the Discrepancy Evaluation Model (DEM) covering five stages: definition, installation, process, product, and program comparison. Data were collected through observations, interviews, and document analysis involving fifth-grade students, teachers, principals, and parents from four public elementary schools. The findings indicate that the policy aligns with the differentiation principles of the Merdeka Curriculum and is supported by institutional readiness through teacher coordination and student data management. Nevertheless, limited communication with parents has led to ethical dilemmas in assessment and a decline in student learning motivation. Overall, the automatic grade promotion policy contributes positively to students’ psychological well-being but requires strengthening through the establishment of minimum competency standards and more effective communication to ensure the quality of learning outcomes.